PERANCANGAN SISTEM MANAJEMEN ARSIP ELEKTRONIK PADA BAGIAN EKSPOR IMPOR DI PT. SEMERU KARYA BUANA - Sunardiansyah, Yogi Akbar; Shoffiyati, Peni; Rahman, Muhammad Fadhlul (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2024)
Record is an important aspect to a company’s administration. In the import export department at PT Semeru Karya Buana, this matter is even more significant because of its role as one of the requirements from government to acquire the economical facilities and advantages as a bonded zone company. In the beginning of 2023, company have a lot of reimport, which needs records’ retrieving related to the transaction. But, because of the inexistence of sufficient record management system, it has become a problem in effectiveness and efficiency. That’s why, the existence of an electronic records management system enables the company to do records-related activities like storing, searching and retrieving of records easier compared to a conventional records management system. The design of this electronic records management system is based on System Development Life Cycle (SDLC) waterfall model and black box testing. The data used in this research are the results of writer’s observation while having the second and third period industrial practice in 2023. The research results show that this electronic archive management system is able to provide a more efficient mechanism for searching and retrieving documents. This system has proven to be a better alternative for archiving activities in the export-import department of PT. Semeru Karya Buana compared to the conventional archiving methods previously used.